Needs Analysis Of Scientific Article Writing Training For English Teachers: A Mixed Method (International Journal of Education and Literature, 2023)
Writing and publishing scientific papers is something that is not only important for researchers, but also for teachers who teach in junior high to high school related to the need to increase teacher professionalism. Therefore, this study aims to analyze the need for training in the ability to write scientific articles in English teachers. This research employs mixed methods whereby quantitative data analysis will be supported by qualitative analysis. Purposive random sampling was used in the selection of research respondents which involved 30 teachers as a sample of a total of 150 English teacher population. This analysis was carried out based on the factors that can affect the difficulty of the process of writing scientific papers including the writing environment; obstacles caused by the topic of writing; the author’s motivation; and the processes, knowledge, and skills involved in writing. The results of this study are expected to be able to become a reference in developing writing training, especially for English teachers and can be an evaluation for teachers about the actions that must be taken to develop the ability to write scientific pap